Residents’ perceptions and attitudes towards sustainable tourism development: The case of Larnaca, Cyprus - Spanou-Tripinioti, Elena; Saveriades, Alexis; Farmaki, Anna (My University, 2018)
It has been argued that residents’ perceptions and attitudes towards tourism development in Island destinations is important for their future sustainability. This study aims to examine residents’ perceptions and attitudes towards sustainable tourism development by focusing on the city of Larnaca, Cyprus. Through a mixed method approach, this study yields insights on residents’ perceptions and attitudes towards sustainable tourism development, particularly in relation to the socio-cultural impacts of tourism. Residents recognise the role that the developmental limitations of small Island destinations play on the formation of their attitude. Conclusively, this study contributes a theoretical framework which tourism planners in Island destinations utilise to evaluate future tourism projects and strengthen residents’ participation in the decision-making process.
Keywords: Sutainable tourism; Cyprus; Larnaca; Residents' perceptions; Island destination